Association between admission hypothermia and outcomes in very low birth weight infants in China: a multicentre prospective study - Yong-hui Yu; Li Wang; Lei Huang; Li-ling Wang; Xiao-yang Huang; Xiu-fang Fan; Yan-jie Ding; Cheng-yuan Zhang; Qiang Liu; Ai-rong Sun; Yue-hua Zhao; Guo Yao; et al. (BMC, 2020)
Abstract Background The objective of this prospective, multicentre, observational cohort study was to evaluate the association between admission hypothermia and neonatal outcomes in very low-birth weight (VLBW) infants in multiple neonatal intensive care units (NICUs) in China. Methods Since January 1, 2018, a neonatal homogeneous cooperative research platform-Shandong Neonatal Network (SNN) has been established. The platform collects clinical data in a prospective manner on preterm infants with birth weights (BWs) < 1500 g and gestational ages (GAs) < 34 weeks born in 28 NICUs in Shandong Province. These infants were divided into normothermia, mild or moderate/severe hypothermia groups according to the World Health Organization (WHO) classifications of hypothermia. Associations between outcomes and hypothermia were tested in a bivariate analysis, followed by a logistic regression analysis. Results A total of 1247 VLBW infants were included in this analysis, of which 1100 infants (88.2%) were included in the hypothermia group, 554 infants (44.4%) in the mild hypothermia group and 546 infants (43.8%) in the moderate/severe hypothermia group. Small for gestational age (SGA), caesarean section, a low Apgar score at 5 min and intubation in the delivery room (DR) were related to admission hypothermia (AH). Mortality was the lowest when their admission temperature was 36.5 ~ 37.5 °C, and after adjustment for maternal and infant characteristics, mortality was significantly associated with AH. Compared with infants with normothermia (36.5 ~ 37.5 °C), the adjusted ORs of all deaths increased to 4.148 (95% CI 1.505-11.437) and 1.806 (95% CI 0.651-5.009) for infants with moderate/severe hypothermia and mild hypothermia, respectively. AH was also associated with a high likelihood of respiratory distress syndrome (RDS), intraventricular haemorrhage (IVH), and late-onset neonatal sepsis (LOS). Conclusions AH is still very high in VLBW infants in NICUs in China. SGA, caesarean section, a low Apgar score at 5 min and intubation in the DR were associated with increased odds of hypothermia. Moderate/severe hypothermia was associated with mortality and poor outcomes, such as RDS, IVH, LOS.